PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN PROPOSAL PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) BERBASIS PENDAMPINGAN INTENSIF DI SEKOLAH BINAAN - Hawariyun, Hawariyun (Jurnal Manajemen Pendidikan, 2018)
Based on observations on the competencies of the Guided School Teachers in compiling the Classroom Action Research Proposal, it was found a phenomenon that the teacher's ability to prepare classroom action research was still low. The purpose of this study was to describe and obtain information about improving the ability of teachers to develop Classroom Action Research Proposals through the CLCK coaching model (Examples, Training, Control, Independent Work) Based on Intensive Mentoring in Foster Schools. This research is a school action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of the study consisted of 5 built school teachers. The research data was collected using an observation sheet. Data were analyzed using percentages. Based on the results of the research and discussion, it can be concluded that the model of Intensive Mentoring based CLCK can improve the ability of teachers in compiling Classroom Action Research Proposals in Foster Schools. Analysis of the quality of PTK proposals made by the teacher shows that the teacher's ability to prepare a Class Action Research Proposal increases from cycle I to cycle II. The teacher's ability to prepare a Class Action Research Proposal in the first cycle is 71.50 (sufficient) to increase to 93.00 (good) in cycle II.